Methodology for the development of blended learning support virtual courses - Medina-Chicaiza, Ricardo Patricio; López-Sevilla, Galo Mauricio; Chiliquinga-Véjar, Lorena del Carmen; González-Hernández, Walfredo; Gavilanes-López, Wilma; Arroba-Bermeo, Ítalo Rosendo (Journal of Posthumanism, 2025)
The article addresses the problem of course development in virtual teaching and learning spaces by teachers. For this purpose, a documentary analysis on blended learning and development of virtual courses was carried out, which allowed defining these two concepts. Subsequently, based on them, the methodology that contributed to the development of courses in virtual spaces as a support to blended learning is proposed.